THE IMPACT OF IPROVE CULTURE TOWARDS THE PERFORMANCE OF THE EMPLOYEES OF SNVT PJPA SUMATERA VIII BANGKA BELITUNG PROVINCE - Agus Maya Sari; Reniati Reniati; Etty Puji Lestari (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
Coming late, coming home too early, and absent from work are part of the employee's problems at Sumatra's SNVT PJPA VIII, Bangka Belitung Province. Work behavior, such as are undisciplined, irresponsible for the job description, shows that the work culture is not fully implemented in the work life of the employee. The work culture of IPROVE (Integrity, Professionalism, Mission Orientation, Visionary and Ethics) should be used as a guideline for the Ministry of Public Works and Public Housing employees in Sumatera's SNVT PJPA VIII of Bangka Belitung Province to performance effectively. This study aims to determine the impact of IPROVE culture both partially and simultaneously. This type of research is a quantitative research using quantitative descriptive methods. The results shows that all research hypotheses are accepted where the IPROVE culture has a positive and significant effect on performance both partially and simultaneously. The order of influence of independent variables on the dependent variable based on the size of Adjusted R Square are integrity of 43.6%, mission orientation of 43.5%, visionary of 37%, ethics of 26% and professionals of 25.7%. Simultaneously work culture of IPROVE affects 48 % of employee performance.